Penerapan Quality Function Deployment (QFD) Dalam Mendesain Ulang Alat Cabut Singkong Otomatis - Susanti Sundari; Aam Wahyu Pratama; Ghapur Hidayat; Suharto Suharto (Fakultas Teknik Universitas Tulang Bawang, 2023)
In this research, the concept of designing a tool for automatically pulling cassava using the Quality Function Deployment (QFD) method is intended to design a cassava pulling tool by considering the needs and customer wants of cassava farmers as tool users. The aim of the research is to redesign the initial concept which is a continuation of previous research that carried out, because design activities or product design are important and absolute things to do before the production process and with QFD can be designed and developed the new products that are able to integrate quality into designs that meet consumer wants and needs which are translated into technical requirements. Based on the results of data processing and analysis, it is known that consumers wants for cassava pulling tools can be described in the customer requirements attribute, where the cassava pulling tool is made of light material, affordable price, can remove more than one stem, the tool is durable, safe to use and has additional functions besides pulling. And the technical characteristics (technical requirements) that influence the tool making process are the capability and strength of the driving machine, the quality of the driving machine, the quality of the light and non-corrosive frame, components for the driving system, the right finishing process. The conclusion from the HOQ analysis shows the greatest weight of importance with a value of 30% where the tool made can remove more than one cassava stem at once. This became the basic reference for developing a redesign of the automatic cassava pulling tool that was made. Keywords: Automatic, cassava pulling tool, design, the Quality Function Deployment